2007
DOI: 10.1111/j.1872-034x.2007.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosed hemangioma of the liver: Report of a case and review of the literature

Abstract: A sclerosed hemangioma of the liver is an extremely rare type of benign hepatic tumor. A 77-year-old female was referred to Tokushima University Hospital with fever, abnormal liver function tests and a large liver mass. The tumor, 10 x 5 cm in size and located in segment 5-6 of the liver, was depicted as a low density tumor with enhancement by computed tomography (CT). Magnetic resonance imaging (MRI) showed it to be a tumor with a low signal on T1-weighted and a high signal on T2-weighted images. The patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
(112 reference statements)
1
22
0
Order By: Relevance
“…In our case, plain CT showed hepatic screlosed hemanangioma as low density, and enhanced CT showed a ring enhancement pattern, which is characteristic of adenocarcinoma. Although cavernous hemangioma shows typical features : low density on plain CT and delayed pooling enhancement, many previous reports have not shown this feature in sclerosed hemangioma (5)(6)(7)(8)(9)(10)(11)(12). MRI finding in our case was fit to typical feature of cavernous hemangioma, such as low on T1 and high on T2 weighted images, but this feature can be also observed in the cases of metastatic liver tumors and cholangiocellular carcinoma.…”
Section: Discussionsupporting
confidence: 65%
“…In our case, plain CT showed hepatic screlosed hemanangioma as low density, and enhanced CT showed a ring enhancement pattern, which is characteristic of adenocarcinoma. Although cavernous hemangioma shows typical features : low density on plain CT and delayed pooling enhancement, many previous reports have not shown this feature in sclerosed hemangioma (5)(6)(7)(8)(9)(10)(11)(12). MRI finding in our case was fit to typical feature of cavernous hemangioma, such as low on T1 and high on T2 weighted images, but this feature can be also observed in the cases of metastatic liver tumors and cholangiocellular carcinoma.…”
Section: Discussionsupporting
confidence: 65%
“…However, this method has a potential risk of abdominal dissemination of tumor cells when the liver mass is malignant. 5 Therefore, we ultimately decided against this option. In recent years, there have been a small number of reports in which DWI and DWI-based ADC were successfully used to detect and differentiate liver tumors.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although Doyle et al 4 have shown the imaging features of 10 SH lesions, the preoperative diagnosis of SH remains problematic. 5 Among the numerous magnetic resonance (MR) sequences available, diffusion-weighted imaging (DWI) has recently been the frequent choice for evaluating liver disease. Previous reports have demonstrated the feasibility of using DWI for the detection and characterization of liver tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Sclerosing hemangioma is a rare type of hepatic hemangioma composed of abundant acellular hyalinized tissue in which small vessels are occasionally seen [1] . Only 17 resected cases, including the present case, with detailed information on patients with hepatic sclerosing hemangioma have been reported in the English literature ( Table 1 ) [3–17] . To the best of our knowledge, this report is the first to describe multiple hepatic sclerosing hemangiomas treated by laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%